2021
DOI: 10.2196/25675
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Students’ Perceptions of Telepractice Services for Speech-Language Therapy During the COVID-19 Pandemic: Survey Study

Abstract: Background The ongoing COVID-19 pandemic has resulted in the suspension of face-to-face classes and a considerable increase in the use of telepractice services in speech-language pathology. However, little is known about parents’ and students’ satisfaction with telepractice services and their preferences for different service delivery modes. These factors may affect therapy effectiveness and the future adoption of telepractice. Objective We evaluated st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…However, usage of telepractice after the first wave was still greater than in the pre-COVID-19 phase. This rapid uptake of telepractice to fill the void in speech-language pathology services created by COVID-19 restrictions is a commonly reported experience for SLPs around the world (Aggarwal et al, 2020;Heiskanen et al, 2021;Lam et al, 2021). Similarly to other research on telepractice during COVID-19, this study found that a wide variety of platforms were used to deliver telehealth services (Aggarwal et al, 2020;Tambyraja et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…However, usage of telepractice after the first wave was still greater than in the pre-COVID-19 phase. This rapid uptake of telepractice to fill the void in speech-language pathology services created by COVID-19 restrictions is a commonly reported experience for SLPs around the world (Aggarwal et al, 2020;Heiskanen et al, 2021;Lam et al, 2021). Similarly to other research on telepractice during COVID-19, this study found that a wide variety of platforms were used to deliver telehealth services (Aggarwal et al, 2020;Tambyraja et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…P rior to March 2020, only 1.6% to 9% of global pediatric speech-language pathology services were provided via telehealth and using telecommunications technologies for synchronous videoconferencing (American Speech-Language-Hearing Association [ASHA], 2020b; Fong et al, 2020;Hill & Miller, 2012;Lam et al, 2021;Mohan et al, 2017;Taylor et al, 2014;Tucker, 2012). Many speechlanguage pathologists questioned the efficacy of telehealth or raised concerns about client comfort (Freckmann et al, 2017;Keck & Doarn, 2014;Lustig, 2012).…”
mentioning
confidence: 99%
“…Speech-language pathologists' negative attitudes, such as the perceived impersonal delivery of services or limited client-caregiver-clinician interactions, represented additional barriers to implementation of telehealth services (Freckmann et al, 2017). Thus, lack of knowledge and training in telehealth as well as speech-language pathologists' perceptions and attitudes about remote service delivery prevented providers from considering synchronous videoconferencing as a viable option for their services (Grillo, 2017;Lam et al, 2021;Taylor et al, 2014).…”
mentioning
confidence: 99%
“…Trotz dieser Bemühungen, auch in schwierigen Zeiten der COVID-19-Pandemie eine kontinuierliche Betreuung zu gewährleisten, müssen wir berücksichtigen, dass nicht alle Patienten bzw. ihre Eltern die teletherapeutische Sprachtherapie so hoch einschätzen wie eine Therapie vor Ort [32]. Darüber hinaus scheint es weit verbreitete Ungleichheiten in der Versorgung mit teletherapeutischer Therapie zu geben.…”
Section: Diskussionunclassified